Exercise training protects against an acute inflammatory insult in mouse epididymal adipose tissue - Castellani, Laura (American Physiological Society, 2014)
Exercise training reduces systemic and adipose tissue inflammation. However, these beneficial effects seem to be largely tied to reductions in adipose tissue mass. The purpose of the present study was to determine if exercise training confers a protective effect against an acute inflammatory challenge. We hypothesized that the induction of inflammatory markers, such as interleukin 6 (IL-6), suppressor of cytokine signaling 3 (SOCS3), and TNF-α by the beta-3 adrenergic agonist CL 316,243 would be reduced in adipose tissue from trained mice and this would be associated with reductions in transient receptor potential cation channel 4 (TRPV4), a protein recently shown to regulate the expression of proinflammatory cytokines. Exercise training (4 wk of treadmill running, 1 h/day, 5 days/wk) increased markers of skeletal muscle mitochondrial content and the induction of PPAR-gamma coactivator 1 alpha in epididymal adipose tissue. The mRNA expression of IL-6, SOCS3, and TNFα were not different in subcutaneous and epididymal adipose tissue from sedentary and trained mice; however, the CL 316,243-mediated induction of these genes was attenuated ∼50% in epididymal adipose tissue from trained mice as were increases in plasma IL-6. The effects of training were not explained by reductions in lipolytic responsiveness, but were associated with decreases in TRPV4 protein content. These results highlight a previously unappreciated anti-inflammatory effect of exercise training on adipose tissue immunometabolism and underscores the value of assessing adipose tissue inflammation in the presence of an inflammatory insult.